The Roots of Misalignment: Insights from a System Dynamics Perspective - Baker, J; Singh, H (Association for Information Systems (AIS), 2015)
Aligning IT strategy with business strategy has repeatedly been shown to yield organizational performance benefits, and is consistently among executives' most important goals. However, as organizations pursue strategic alignment, IT and business strategies often evolve in unintended ways, thereby limiting alignment. In this essay, we review literature to identify reasons why IT and business strategies are often not realized in the manner in which they were originally intended, resulting in misalignment. To model the processes of strategy formation and strategic change, including processes at multiple levels within the organization, we utilize the causal loop diagramming approach of systems dynamics. Our model explains that key reasons for the differences between intended and realized strategies include the limitations of senior managers' communication, the ability of individuals and groups within organizational hierarchies to modify plans developed by senior management, and the reality of environmental dynamism. The primary intended contribution of this paper is the enumeration and modeling of both the top-down processes that can promote or hinder strategic alignment, as well as the less-studied bottom-up processes, ultimately yielding a more nuanced, dynamic, process-oriented understanding of strategic alignment.
Keywords: Strategic alignment; Strategy; Strategic IS planning; Drift; Governance; Process theory; Systems dynamics; Causal loop; Feedback